Boston Catholics A History of the Church and Its People - O'Connor, Thomas H. (Northeastern University Press, 2019)
In this engaging work, Thomas H. O'Connor chronicles the activities, achievements, and failures of the Church's leaders and parishioners over the course of two centuries. Originally published by Northeastern University Press in 1998. With a new foreword by James M. O'Toole.